TEORI-TEORI PENDIDIKAN ISLAM DALAM PENDEKATAN NORMATIVE DOKTRINER, FILOSOFIS, SOSIOLOGIS, ANTROPOLOGIS, PSIKOLOGIS, DAN HISTORIS - Rabi'ah Rabi'ah (Tarbawi, 2023)
This study aims to understand the various perspectives in Islamic education theories through doctrinal-normative, philosophical, sociological, anthropological, psychological, and historical approaches. Utilizing qualitative content analysis methods, this research examines the depth of Islamic education theory based on primary sources such as the Qur'an and Hadith, as well as their interpretations and implementations in the context of contemporary education. From a philosophical approach, this study investigates educational principles aimed at stimulating human intellectual and spiritual capabilities. Meanwhile, the sociological approach discusses the interaction of Islamic education with social dynamics, the anthropological approach focuses on cultural aspects, the psychological approach explores the development of personality and emotions, and the historical approach examines the evolution of educational practices in Islamic history. The findings of this study provide a multidimensional understanding of Islamic education that can serve as a reference for the development of curricula and teaching methods that align with Islamic values and the needs of modern society. The development of Islamic education theories should be holistic or comprehensive in order to educate human resources that are of high quality both scientifically and in terms of personality, as well as to promote a good quality of social life.